La orientación profesional en los sistemas de formación profesional - Sanz López, Clara (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN El artículo hace una revisión documental y bibliográfica de la relación que ha de establecerse entre orientación y formación profesional, y la necesidad de reforzar los mecanismos de apoyo que aumentan las oportunidades de acceso a la formación profesional y al empleo, mediante orientación profesional a corto, medio y largo plazo. La orientación profesional ha tenido menor presencia en Formación Profesional que en estudios académicos generales. Sin embargo, es evidente que la orientación en Formación Profesional debe incorporarse garantizando una atención similar a la que se recibe en un itinerario de carácter general. La reflexión pretende dar respuesta a una serie de interrogantes, tales como si la intervención de los sistemas de orientación en la elección de este itinerario formativo responde a criterios de equidad, y promoción de la igualdad de oportunidades, o refuerzan la marginación de las opciones profesionales; la “ubicación” de la Orientación Profesional en relación a las enseñanzas de Formación Profesional (FP); los contenidos a abordar antes de la elección, durante y al finalizar los estudios de FP; las necesidades de formación inicial y/o continua de los orientadores para realizar una prestación de calidad en FP; o la identificación de los aspectos que permitirían acortar las transiciones entre formación y trabajo para los titulados de FP. ABSTRACT The article is based on a documentary and bibliographical review of the relation that has to be established between guidance and vocational training. A fundamental line of action is to strengthen support mechanisms to increase the opportunities of access to vocational education and training and to jobs. This can be done by means of career guidance, not just for the short term (reintegration into the workplace), but for the medium and long term as well. Thus far, career guidance has clearly received less attention in vocational education and training than in general academic studies. It is assumed that decisions about training and vocational pathways have already been taken by the time a person embarks on VET. The reflection tries to respond to a series of questions: Do counselling practices implemented at the moment of choosing a path uphold the criteria of equity and equal opportunities, or do they help assign students to pathways according to narrow criteria and reinforce the marginalisation of vocational options? What is the “rightful place” of career education in connection with vocational and educational training? What contents should career guidance focus on at different points in the process (before VET studies are chosen, during VET studies, at the end of vocational training)? What are the initial and/or continuing education and training needs of guidance practitioners in order to provide quality in the realm of VET? Can any specific guidance action be identified that can shorten the transitions between training and work?